Classroom Interaction Between Physical Education and Virtual Education in The Teaching of Physics - Muhsin, Raid Isam; Ahmed, Salam Malik (Journal of Tikrit University for Humanities, 2023)
The aim of the research is to identify the classroom interaction between physical education and virtual education in the teaching of physics, and to know the impact of gender and number of years of experience variables on teachers’ opinions about this classroom interaction. The descriptive survey method was used, and the research sample consisted of all male and female physics teachers in (26) preparatory schools in the city of Tikrit, the center of Salah al-Din Governorate - Iraq, who numbered (60) male and female teachers, that is, by (100%), and the research tool relied on the questionnaire and was divided into two axes (classroom interaction during attendance education, classroom interaction during virtual education) and it consisted of (30) paragraphs. Physics see the case of classroom interaction, whether through physical education or virtual education, to a large extent, this subject is taught in middle schools in the city of Tikrit.